Medicinal plants and compounds for chronic bronchitis treatment: efficacy and action mechanisms - Ding, Wei; Chen, Danni; Li, Jiawang; Wang, Yan; Chen, Xiangyun; Xu, Yihe; Yang, Zhen; Liu, Zhenhong; Zhao, Hongxia (Frontiers in Pharmacology, 2025)
BackgroundChronic bronchitis (CB) is a common yet heterogeneous condition characterized by persistent inflammation, oxidative stress, airway hyperresponsiveness, and mucus hypersecretion. As an early stage of various severe pulmonary diseases, current therapeutic strategies remain unsatisfactory. Substantial evidence indicates that medicinal plants and compounds hold potential for treating inflammatory lung disorders. This study aims to consolidate recent and reliable evidence concerning the multi-targeted roles and underlying molecular mechanisms of these natural products in the treatment of CB.MethodsThis systematic review followed a prospectively registered protocol (PROSPERO ID: CRD42024588912). A comprehensive literature search encompassed multiple electronic databases, including PubMed, Scopus, Embase, Web of Science, VIP, Wan-fang, SinoMed, and the China National Knowledge Infrastructure Study selection strictly adhered to the PICOS principles to systematically identify medicinal plants and compounds with therapeutic potential against Chronic bronchitis.ResultsThe results identified 13 medicinal plants and 19 compounds that exhibited anti-inflammatory activity. Additionally, 8 plants and 12 compounds demonstrated further therapeutic effects, including antioxidant, anti-mucus, and potential bronchodilatory activities. The underlying mechanisms primarily involved the NF-κB, PI3K/AKT/mTOR, TLR4, MAPK, and Nrf2 pathways. Ursolic acid emerged as the most promising clinical candidate.ConclusionThis review represents the first comprehensive synthesis of experimentally verified efficacy and mechanisms associated with medicinal plants and compounds in CB treatment. Preclinical animal studies have confirmed the therapeutic benefits of these natural agents in alleviating CB symptoms, establishing a solid foundation for novel drug development and underscoring their considerable translational potential.